On the issue of coordination of the activities of forces and means of organizations and institutions of the Federal Medical and Biological Agency of Russia and Rospotrebnadzor in emergency situations of a radiation nature - A. S. Samoilov; I. K. Romanovich; M. I. Grachev; Yu. A. Salenko; A. N. Barkovsky; V. S. Repin; L. S. Bogdanova (Радиационная гигиена)
The article identifies areas of joint activities and mechanisms of interaction of Federal Service for Surveillance on Consumer Rights Protection and Human Wellbeing (Rospotrebnadzor) and Federal Medical and Biology Agency (FMBA of Russia), their territorial bodies and institutions in the event of radiation accidents. Extensive practical experience gained by specialists of FMBA of Russia and Rospotrebnadzor, was the basis for the development of the draft of Concept “Organization of radiation and hygienic measures in emergency situations of a radiation nature and coordination the activities of forces and means of FMBA of Russia and Rospotrebnadzor organizations and institutions” (2018). The article presents the main provisions of the draft document, which, after discussion and refinement, as the authors hope, this publication will contribute, draft of Concept can be submitted for approval. The modern infrastructure of Rospotrebnadzor and FMBA of Russia has all the necessary elements and prerequisites for coordinated work of expert support groups, use of the mobile specialized radiation-hygienic teams in emergency situations. The possible types of radiation accidents that may require joint activities of the bodies and institutions of Rospotrebnadzor and FMBA of Russia are considered. In the initial period of a radiation accident in conditions of large uncertainties related to the assessment of the radiation situation and doses on personnel and the public, it is necessary to ensure operative preparedness of consolidated proposals on making decisions on a complex of sanitary, hygienic, anti-epidemic and protective measures. Much attention is paid to mutual notification and information interaction. An important element in ensuring emergency preparedness, working out algorithms of the interaction of management bodies and practical skills of the personnel of Rospotrebnadzor and FMBA of Russia is the joint planning, organization and conduct of training and exercises.